IMPROVING BASIC MOVEMENTS AND HEALTH OF MENTALLY DISABLED STUDENTS THROUGH ADAPTIVE PHYSICAL ACTIVITIES - Sumaryanti, Sumaryanti; Rahayu, Tandiyo; Amirullah, Hari; Rahayu, Setya; Rukmini, Dwi (Universitas Negeri Semarang, 2013)
The research aims at developing a learning model of adaptive physical activities(APA) for improving basic movements and health of mentally disabled students ina disabled elementary school at Bantul regency; therefore it is a research and development.There are 5 steps used by the researcher : a preliminary study, planning,expert validation, empirical validation and effectiveness testing. The small scale implementationtesting was done to 13 disabled students whereas the large scale, 42students of 3 graders of disabled elementary school. The effectiveness testing usesan experimental research within one pre and post test group. The group consists of27students of Plered Disabled Elementary School. The research observation instrumentuses Likert scale and ratting-scale. The proposed learning models are: KidKomodo football, waves in the sea, knowing shapes, frog circus and air bubble.These models prove effective for mentally students of disabled elementary school.Both the small scale implementation testing and the large scale one result in theimprovement of basic physical movements of the students. The secondary result isthat teachers of physical education and health find the models easy to do and thestudents get fun being taught using them.